The Role of BAZNAS and Pesantren-Based Colleges on the Empowerment of Education in STIBA Ar Raayah - Husnul Khatimah; Nuradi; Irfan Syauqi Beik (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2024)
This study aims to determine the role of BAZNAS and Pesantren-Based College on education empowerment in STIBA Ar Raayah for students receiving BAZNAS scholarship assistance. This study uses a quantitative descriptive method with descriptive statistical data analysis techniques SPSS 24.0 for Windows to measure the path of analysis path (causal relationship) between the independent variables (the role of empowerment and pesantren-based universities) to the dependent variable (education empowerment). The sampling technique used is a saturated sampling technique, which makes all the population respondents that as many as 37 recipients of BAZNAS scholarship assistance from alums and those who still belonged as STIBA Ar Raayah students who have filled out a questionnaire through the Google form. The results showed that BAZNAS had a significant role in the Empowerment of Education based on the results of the ANOVA analysis, which was indicated by a significance value of 0.000 <0.05. At the same time, Pesantren-Based University, or in this case, STIBA Ar Raayah, had not played a significant role in the students receiving BAZNAS scholarship assistance, which was marked with a significance value of 0.235 > 0.05.